Perbedaan Homesicknes Pada Siswa Tahun Pertama, Kedua dan Ketiga di Pesantren - Natalia Vamelia; Maya Yasmin (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to determine the difference in homesickness in first, second and third year students in Islamic Boarding School. The number of subjects involved is as many as 300 students, 100 first-year students, 100 second-year students and 100 third students who live in Islamic Boarding School. The sampling technique used is Cluster random sampling which is taken based on sub-districts in Agam district. Homesickness was measured using the Homesickness scale compiled by researchers based on the dimensions of homesickness from Stroebe, et al (2002). The results showed that there were differences in homesickness between first, second and third year students in Islamic Boarding School. Where first-year students experience homesickness with the highest percentage (86,79%), second-year students (67,11%) and third-year students (53,21%).